Bursts of seizures in long‐term recordings of human focal epilepsy. (13th January 2017) - Karoly, Philippa J.; Nurse, Ewan S.; Freestone, Dean R.; Ung, Hoameng; Cook, Mark J.; Boston, Ray
Summary: Objective: We report on temporally clustered seizures detected from continuous long‐term ambulatory human electroencephalographic data. The objective was to investigate short‐term seizure clustering, which we have termed bursting, and consider implications for patient care, seizure prediction, and evaluating therapies. Methods: Chronic ambulatory intracranial electroencephalography (EEG) data collected for the purpose of seizure prediction were annotated to identify seizure events. A detection algorithm was used to identify bursts of events. Burst events were compared to nonburst events to evaluate event dispersion, duration and dynamics. Results: Bursts of seizures were present in 6 of 15 subjects, and detections were consistent over long‐term monitoring (>2 years). Subjects with bursts of seizures had highly overdispersed seizure rates, compared to other subjects. There was a complicated relationship between bursts and clinical seizures, although bursts were associated with multimodal distributions of seizure duration, and poorer predictive outcomes. For three subjects, bursts demonstrated distinctive preictal dynamics compared to clinical seizures. Significance: We have previously hypothesized that there are distinct physiologic pathways underlying short‐ and long‐duration seizures. Herein we show that burst seizures fall almost exclusively within the short population of seizure durations; however, a short duration event was not sufficient to induce or imply bursting. We can therefore conclude that in addition to distinct mechanisms underlying seizure duration, there are separate factors regulating bursts of seizures. We show that bursts were a robust phenomenon in our patient cohort, which were consistent with overdispersed seizure rates, suggesting long‐memory dynamics.